Glycoproteomic Study Reveals Altered Plasma Proteins Associated with HIV Elite Suppressors - Yang, Weiming (Ivyspring International Publisher, 2014)
HIV elite suppressors (ES) or controllers are individuals achieving control of viremia by their natural immunological mechanisms without highly active antiretroviral therapy (HAART). Study of the mechanisms responsible for the immunological suppression of viremia in ES may lead to the detection of individuals with ES and the effective control of HIV infection. We hypothesize that plasma glycoproteins play essential roles in the immune system of ES since plasma proteins are critical and highly relevant in anti-viral immunity and most plasma proteins are glycoproteins. To examine glycoproteins associated with ES, plasma samples from ES individuals (n=20), and from individuals on HAART (n=20), with AIDS (n=20), and no HIV infection (n=10) were analyzed by quantitative glycoproteomics. We found that a number of glycoproteins changed between ES versus HAART, AIDS and HIV- individuals. In sharp contrast, the level of plasma glycoproteins in the HAART cohort showed fewer changes compared with AIDS and HIV- individuals. These results showed that although both ES and HAART effectively suppress viremia, ES appeared to profoundly affect immunologically relevant glycoproteins in plasma as consequence of or support for anti-viral immunity. Bioinformatic analysis revealed that altered proteins in ES plasma were mainly associated with inflammation. This analysis suggests that overlapping, while distinguishable, glycoprotein profiles for inflammation and immune activation appeared to be present between ES and non-ES (HAART+AIDS) cohorts, indicating different triggers for inflammation and immune activation between natural and treatment-related viral suppression.